MEDIA JAM SUDUT PINTAR: PENGEMBANGAN, VALIDASI, DAN UJI COBA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA SISWA SD: Media Pembelajaran Jam Sudut Pintar - maryani, Nurul; Mohammad Edy Nurtamam; Ahmad Sudi Pratikno; Ana Naimatul Jannah (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
This research aims to develop Smart Corner Clock learning media to improve students' problem-solving skills in grade V elementary school angle measurement material. The background of this research began from the results of observations and interviews at SDN Ketetang 1 which showed that mathematics learning was still dominated by lecture methods without concrete media, so that students had difficulty understanding the concept of angles. The method used is Research and Development (R&D) with a 4D model (Define, Design, Develop, and Disseminate), but only up to the Develop stage. The subject of the study is a student of class V-B SDN Ketetang 1. Data was obtained through interviews, student needs questionnaires, observations, and validation and response questionnaires. The validation results showed that the Smart Corner Clock media was classified as very valid, with a percentage of validation of material experts of 88.63%, learning design experts of 95.58%, and learning media experts of 90.21%. The results of the limited trial showed 88.33% student activity, 95.83% teacher activity, and 87.5% student response, while large group trials showed that teacher and student activity was in the range of 79.16%–89.58%. The results of the evaluation test showed an increase of 16.46% after using the Smart Angle Clock media. Based on these results, it can be concluded that the Smart Corner Clock media is valid, interesting, and effective in mathematics learning to help students understand angular concepts concretely and improve problem-solving skills.